FDA-approved thiol-reacting drugs that potentially bind into the SARS-CoV-2 main protease, essential for viral replication - Diaz Sanchez, Angel Gabriel (2020)
Emergent novel SARS-CoV-2 is responsible for the current pandemic outbreak of severe acute respiratory syndrome with high mortality among the symptomatic population worldwide. Given the absence of a current vaccine or specific antiviral treatment, it is urgent to search for FDA-approved drugs that can potentially inhibit essential viral enzymes. The inhibition of 3CLpro has potential medical application, due to the fact that it is required for processing of the first translated replicase polyproteins into a series of native proteins, which are essential for viral replication in the host cell. We employed an in silico approach to test if disulfiram, as well as its metabolites, and captopril could be used as potential antiviral drugs against COVID-19. We provide data on the potential covalent interaction of disulfiram and its metabolites with the substrate binding subsite of 3CLpro and propose a possible mechanism for the irreversible protease inactivation thought the reaction of the aforementioned compounds with the Cys145. Although, captopril is shown to be a potential ligand of 3CLpro, it is not recommended anti-COVID-19 therapy, due to the fact that it can induce the expression of the viral cellular receptor such as, angiotensin-converting enzyme ACE-2, and thus, making the patient potentially more susceptible to infection. On the other hand, disulfiram, an alcoholism-averting drug, has been previously proposed as an antimicrobial and anti-SARS and MERS agent, safe to use even at higher doses with low side effects, it is recommended to be tested for control of SARS-CoV-2 infection.